Keanekaragaman Kapang Udara di Ruang Perkuliahan Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Tanjungpura Pontianak - Riza Linda, Noriami Simanjuntak, Siti Khotimah, (Universitas Tanjungpura, 2015)
Air molds are microorganisms found in the air in the form spores, hifa, or misellium. This research is intended to find out the type of air molds discovered in ten lecture rooms each using either Air Conditioners or fans, conducted from December 2014 to April 2015. The method used in this research is Air Sampling method. The data gained is shown in both visually and descriptively. The research’s result has found fifteen species of air molds. There are six species found in the lecture rooms which use AC, they are Aspergillus clavatus, A. niger, Cladosporium cladosporioides, Curvularia lunata, Cylindrocarpon olidum, and Penicillium funiculosum, with environmental factors are the temperature of 27-29’C, humadity of 80-92%, and light intensity of 66-252 Lux. While the lecture rooms using fans has twelve species of air molds, consist of Acremonium charticola, Aspergillus candidus, A. flavus, A. niger, Bipolaris australiensis, C. cladosporioides, C. clavata, P. chrysogenum, P. citrinum, P. funiculosum, P. variabile and Phytophthora capsici, with its supporting environmental factors are temperature of 30-31’C, humidity of 75-338 Lux. But the lecture rooms using AC and fans has three the same species of air molds, consist of A. niger, C. cladosporioides, and P. funiculosum.